Professor Percival R. Kirby, M.A., D.LITT., F.R.C.M., D.MUS. HON. (International Library of African Music, 1970)
Professor Kirby came to South Africa from Britain in 1914 to be Inspector of Music in Natal. He was one of the earliest musicologists to take a special interest in African music. As Professor of Music at the University of the Witwatersrand, Johannesburg, he undertook several journeys into the country in the early 1930's to study the indigenous musics of South Africa under the auspices of the Carnegie Corporation of New York.
Keywords: African Music